Innovation of VARK Modality-Based Differentiated Learning: Development of Social Studies Instructional Toolkit for Junior High School - Ismi Octaviani; Etin Solihatin; Uwes Anis Chaeruman (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: The present study aimed to develop a differentiated instructional toolkit grounded in Neil Fleming's VARK (Visual, Aural, Read/Write, Kinesthetic) modalities for grade VII social studies, specifically on economic activity materials. Methodology: The study employed a Research and Development design following the ASSURE model (Analyze Learners, State Objectives, Select Methods, Media, and Materials, Utilize Media and Materials, Require Learner Participation, Evaluate and Revise). The research took place at SMP Nusantara 1 Tangerang and involved 79 grade VII students during the even semester of the 2025/2026 academic year. Data collection instruments included expert validation questionnaires, student response questionnaires, and pre-test/post-test assessments.Main Findings: The findings indicated that the developed instructional toolkit, which consisted of a teaching module, learning materials, student activity worksheets, interactive media, and assessment instruments, received a